Intertextuality in Mohamad Al-Qysi Poets - Nida' Ali Yousef Ismaeel (My University, 2012)
This study sheds light on the allusion in Mohamad Al-Qaysy' poetry. The study consists of introduction , sex chapters and conclusion. The introduction contains the biography 0f the poet, his poetry and the resources of his works. Chapter one identifies the allusion and its importance , the term according to the Western criticisms' viewpoints , allusion in the Arabs heritage works and the recent Arabs criticisms' visions . Chapter two contains the religious allusion in Al-Qaysy's poetry stemmed from the Holy Books , particularly, the prophets' stories in the Holy Qur'an and traditions . Literature allusions included in the third chapter and its effects on his poetry experience. The previous poets' experiences have been studied and restructured in his experience which enriched his poetry and made harmony between the past and the present. Historical allusion with its actions, setting and characters has been emphasized in the fourth chapter in order to improve the Palestinian rights on the Palestinian land. Chapter five clarifies the popular and legendary allusion . The features of this kind is exemplified throughout several kinds like legends, songs, fables, tales, and even throughout the traditions and customs. The importance of the historical allusion has raised to be a tool which has its meanings of values and contents. The conclusion clarifies the researcher's vision throughout the results.

تدور هذه الأطروحة حول التناص في شعر "محمد القيسي"، حيث اشتملت على تمهيد، وخمسة فصول، وخاتمة، تناولت الباحثة في التمهيد سيرة حياة الشاعر، ثم بينت بإيجاز شاعريته، وبعد ذلك انتقلت للحديث عن أهم المصادر التي استقى منها مادته الشعرية، ثم الحديث عن نشأة المصطلح عند النقاد الغربيين والعرب. احتوى الفصل الأول على التناص الديني في شعر القيسي، وما تضمنه من نصوص وردت في الكتب المقدسة (القرآن الكريم، والإنجيل، والتوراة) يضاف إلى ذلك تناصه مع الحديث النبوي الشريف. اشتمل الفصل الثاني على التناص الأسطوري بمصادره المختلفة التناص مع الأسطورة المحلية والتناص مع الأسطورة اليونانية. أمّا الفصل الثالث فقد اشتمل على التناص الأدبي، وأثره في صياغة تجربة محمد القيسي الشعرية، حيث استوعب القيسي تجارب الشعراء السابقين ومضامينهم، وأعاد تمثلها في تجربته الشعرية، مما أثرى نصوصه الشعرية، وجعلها قادرة على تحقيق توافق بين الماضي والحاضر. اشتمل الفصل الرابع على التناص التاريخي، وما تضمنه من تناص مع الأحداث والأماكن والشخصيات التاريخية، والتي استحضرها في شعره؛ لما لها من خصوصية تظهر من كونها محوراً في إثبات الحق الفلسطيني في هذه الأرض. أمّا الفصل الخامس فاشتمل على التناص الشعبي ، ولعل أهم ما يميز هذا الاستحضار تنوعه، فاشتمل على الأغاني، والحكايات، والأمثال و العادات والتقاليد، وتبرز أهمية هذا التناص في كونه وسيلة لها إيحاءاتها الشكلية والمضمونية. وتأتي الخاتمة في نهاية الدراسة لتلخص رؤية الكاتبة حول كل ما تم دراسته، وذلك من خلال عرضها للنتائج التي توصلت إليها.
التناص في شعر محمد القيسي